Limites para a imputação de responsabilidade penal decorrente de decisões embasadas em pareceres técnicos e jurídicos - Torres, Tiago Caruso (2018)
At present, laws and regulations with volatile and complex content has removed from who has the power to decide the technical or legal knowledge necessary to understand if his project of conduct is licit or not. The intense number of legal and extra-legal regulations and the complexity of the matter to be regaled make the necessity to decisions be previously supported by specialized opinions or consultancies. In such situations, the dependence on information about the regularity and legality of the decision fragments, on the one hand, the power of the decision and, on the other hand, the qualified technical or legal knowledge in cases that involve complex and strategic situations in private corporate structures or in public administration structures. For this reason, what in Classical Criminal Law was understood as an internal mental process of one person that externalize his conduct in a harmful result, happens, nowadays, in a fragmented way in Economic Criminal Law. As a consequence, it is no longer possible to return this harmful result to only a single will. In these situations, the problem arises when, in the end, it is verified tha the harmwful result results from a decision that was taken based on an erroneous technical or legal opinion. In these situations, it is necessary to verify if who took the decision supported by prior technical or legal opinion has criminal responsibility and if there is a criminal responsibility to be assigned to the specialist who has advised that decision. After, it is important to explain how they can be criminally held accountable. These are the questions that the present study intends to answer, as a contribution to clarify these cases that seems not to have been well understood by the criminal theory